2022
DOI: 10.1155/2022/8781489
|View full text |Cite
|
Sign up to set email alerts
|

Study on Occupancy Behaviors of Passengers in the Subway Cabin: An Observation in Chengdu, China

Abstract: Insufficient attention has been paid to how subway cabins are used by passengers and especially the distribution of passengers and occupancy of facilities. In this study, passengers were observed in 133 sections from the beginning to the end of the early peak of Chengdu Metro in the working days. The differences in occupancy behaviors of passengers to different areas, seats, and standing auxiliary facilities in the cabin were analyzed by the nonparametric test. The occupancy curve was fitted by the least squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(88 reference statements)
0
0
0
Order By: Relevance
“…Recent studies have shown the distribution of passengers and their interaction based on variables such as queue length at the door, number of people inside the carriage, travel distance, and comfort of passengers [31]. The space of passengers and the occupation inside the train are reported in [32,33], which are essential factors that affect the interaction of passengers boarding or alighting. The characteristics of passengers are also studied in [34] utilizing laboratory experiments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent studies have shown the distribution of passengers and their interaction based on variables such as queue length at the door, number of people inside the carriage, travel distance, and comfort of passengers [31]. The space of passengers and the occupation inside the train are reported in [32,33], which are essential factors that affect the interaction of passengers boarding or alighting. The characteristics of passengers are also studied in [34] utilizing laboratory experiments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Urban subways, renowned for their speed and capacity, are prevalent across 79 countries, including Japan, the United States, Korea, China, Brazil, Chile, and Colombia [1,2]. Globally, subway networks spanned approximately 36,854.20 km in 2021, facilitating nearly 39.67 billion passenger journeys [3].…”
Section: Introductionmentioning
confidence: 99%